2018
DOI: 10.1108/jaee-01-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards accounting and intention to major in accounting: a logistic regression analysis

Abstract: Purpose The purpose of this paper is to examine the attitude of business students towards the accounting profession and investigate the relationship between students’ attitude and their intention to pursue a degree in accounting. Design/methodology/approach A self-administered survey was used to collect data from students from the University of Ghana Business School (UGBS). A total of 457 questionnaires were used in the empirical analysis. A binary logistic regression analysis technique was employed to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 27 publications
(56 reference statements)
6
46
0
Order By: Relevance
“…The results of hypothesis testing are supported by several previous studies (Wen, Yang, Bu, Diers, & Wang, 2018;Bekoe et al, 2018;Dos Santos & De Almeida, 2018). They found that accounting students' decision to choose an accounting career was significantly influenced by their attitudes toward the profession of accounting.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The results of hypothesis testing are supported by several previous studies (Wen, Yang, Bu, Diers, & Wang, 2018;Bekoe et al, 2018;Dos Santos & De Almeida, 2018). They found that accounting students' decision to choose an accounting career was significantly influenced by their attitudes toward the profession of accounting.…”
Section: Resultssupporting
confidence: 78%
“…The resulting goal may stimulate them to act (Lent et al, 2000). Several previous studies by Mbawuni (2015); Bekoe et al (2018), and Dalcı and Özyapıcı (2018) found that perception was able to affect someone's career choices. Santos and Almeida (2018) agreed that the perception of accounting students on the accountant, or accounting work, was important in influencing selfimage, belief, and attitude towards the accounting profession.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even before, Awayiga, Onumah, and Tsamenyi (2010) had examined the accounting knowledge and skills required by graduates. Other empirical studies conducted in Ghana had being on quality of accounting education (Kwarteng, 2014), professional qualification and instructional practices of accounting curriculum (Osei-Tutu & Darkwa, 2015), gender and accounting education in Ghana (Aboagye, 2016) as well as students' attitude toward the study of accounting and performance (Bekoe, Owusu, Ofori, Essel-Anderson & Welbeck, 2018). Clearly there exists a space in knowledge regarding preservice teachers' influx to the teaching profession.…”
Section: Introductionmentioning
confidence: 99%
“…It is public knowledge that a lot of career opportunities exist within the accounting profession (Cooper et al, 2020;Bekoe et al, 2018;Anderson-Gough, 2002). These include audit, tax, financial reporting, business advisory, etc.…”
Section: Introductionmentioning
confidence: 99%